Does Reacting to the Past Increase Student Engagement? An Empirical Evaluation of the Use of Historical Simulations in Teaching Political Theory. Issue 1 (2nd January 2017) - Weidenfeld, Matthew C.; Fernandez, Kenneth E.
ABSTRACT: Within the teaching of political theory, an assumption is emerging that Reacting to the Past simulations are an effective tool because they encourage greater student engagement with ideas and history. While previous studies have assessed the advantages of simulations in other political science subfields or offered anecdotal evidence of their effectiveness in political theory courses, less attention has been paid to the empirical assessment of simulations in political theory. This study uses data — in the form of presimulation and postsimulation surveys, as well as focus groups — collected from two political theory courses in order to gauge levels of student engagement inside and outside of the classroom. We ask if students' levels of engagement increase during the simulation in their political theory courses. We also explore the mechanisms involved in driving higher levels of student engagement during the simulation. We conclude by arguing that it is the liminal nature of the Reacting to the Past simulations that most likely explains increased levels of student engagement.